Comportamiento del sector turismo, industria hotelera en las regiones de selva baja en el periodo 2018 - 2022 - Pasquel Barrera, Beny Alexander (2023)
In the regions of Loreto, San Martín and Ucayali, tourism is insufficiently developed, there are few tourist places that are promoted in each region, Pacaya Samiria Reserve, Alpahuayo Mishana, San Mateo terminal baths, Tioyacu source, Ducha del Diablo and Velo de girlfriend; The San Martín region stands out in terms of the number of tourists served, which almost doubles the other two regions. The categorized accommodations that have the greatest preference in the regions of Loreto and Ucayali are those with three and two stars and in the Ucayali region the preference is in three and four-star accommodations. The year 2020 was the year that the tourism sector was affected due to the COVID-19 pandemic, several tourist attractions were no longer visited and the recovery is slow. By 2022, the number of tourists that were served in the country has not yet been reached. In 2019, it is necessary for tour operators and the Ministry of Foreign Trade and Tourism (MINCETUR) to carry out a viable and sustainable Strategic Plan.